Lithosperic-scale transcurrent fault systems in Andean southern Peru - Sempere, Thierry (2002)
Although Andean southern Peru forms the northwestern termination of the Bolivian Orocline, knowledge of its geology has little progressed in the last 20 years, partly due to the civil war that spread in the region during the 1980s and early 1990s. As a consequence, outdated information and concepts are generally still used in current assessments and syntheses, and updated data are needed. This short descriptive contribution presents the principal tectonic elements we currently recognize in southern Peru, and their relationships with syntectonic sedimentary basins. We observe that the most prominent deformational systems in this part of the Bolivian Orocline are dominantly transcurrent, and that many magmatic manifestations are associated with them.